Combined effects of alpha particles and depleted uranium on Zebrafish ( Danio rerio ) embryos. (3rd August 2016) - Ng, Candy Y.P.; Pereira, Sandrine; Cheng, Shuk Han; Adam-Guillermin, Christelle; Garnier-Laplace, Jacqueline; Yu, Kwan Ngok
Abstract: The combined effects of low-dose or high-dose alpha particles and depleted uranium (DU) in Zebrafish ( Danio rerio ) embryos were studied. Three schemes were examined—(i) [I L U L ]: 0.44 mGy alpha-particle dose + 10 µg/l DU exposure, (ii) [I H U H ]: 4.4 mGy alpha-particle dose + 100 µg/l DU exposure and (iii) [I H U L ]: 4.4 mGy alpha-particle dose + 10 µg/l DU exposure—in which Zebrafish embryos were irradiated with alpha particles at 5 h post fertilization (hpf) and/or exposed to uranium at 5–6 hpf. The results were also compared with our previous work, which studied the effects of [I L U H ]: 0.44 mGy alpha-particle dose + 100 µg/l DU exposure. When the Zebrafish embryos developed to 24 hpf, the apoptotic signals in the entire embryos, used as the biological endpoint for this study, were quantified. Our results showed that [I L U L ] and [I H U L ] led to antagonistic effects, whereas [I H U H ] led to an additive effect. The effect found for the previously studied case of [I L U H ] was difficult to define because it was synergistic with reference to the 100 µg/l DU exposure, but it was antagonistic with reference to the 0.44 mGy alpha-particle dose. All the findings regarding the four different schemes showed that the combined effects critically depended on the dose response to each individual stressor. We also qualitatively explained these findings in terms of promotion of early death of cells predisposed to spontaneous transformation by alpha particles, interacting with the delay in cell death resulting from various concentrations of DU exposure.